Combating terrorism and the use of force against a state: a re-look at the contemporary world order - Hamid, Abdul Ghafur@Khin Maung Sein (2013)
This paper advocates two main arguments: (1) that a terrorist attack may not be an ‘armed attack’ under Article 51 of the UN Charter to justify the use of military force in self-defence if a State is not responsible for it and if the attack is not of such gravity as to amount to an actual armed attack conducted by regular armed forces; and (2) that to use military force against another State is a serious matter that requires a higher threshold of attribution on the part of a State. The paper also argues that international terrorism cannot be wiped out by means of unilateral use of force against a State in the name of self-defence. Unilateralism may lead to subjectivity, selectivity, double standard and injustice.